Social freedom and migration in a non-ideal world. Issue 4 (29th November 2019) - Thompson, Drew
ABSTRACT: In this paper, I identify two key contributions that David Ingram makes to the migration ethics literature, one methodological and one substantive. Ingram's methodological contribution is to model how non-ideal theorizing can be done without abstracting away the complexities surrounding migration, including how the motivation to migrate is tied to existing institutional structures. He does this by beginning with the powerlessness and coercion experienced by certain classes of migrants, which he analyses using a rich conception of agency as social freedom. From here, Ingram develops his substantive contribution. Ingram argues that cosmopolitan and communitarian analyses cannot fully capture the dilemma surrounding forced migration: migrate to improve welfare or remain for the sake of identity and community. Ingram identifies the injustice of borders as occurring within the context of an interconnected international order operating without discursive accountability to most of those affected by its policies. Ingram argues that until international institutions are suitably reformed, asylum is owed to economic refugees because of the coercive circumstances existing in their countries of origin. This allows him to show, too, why specific states have obligations to asylum seekers: because they participate in the institutions that have contributed to these circumstances. Although I agree with Ingram's overall approach, I will question whether he downplays the demands of his conception of social freedom and consider the feasibility of institutionalizing his discourse theoretic framework.